Clinical and Genetic Characteristics of 153 Chinese Patients With X-Linked Hypophosphatemia - Lin, Xiaoyun; Li, Shanshan; Zhang, Zhenlin; Yue, Hua (Frontiers in Cell and Developmental Biology, 2021)
X-linked hypophosphatemia (XLH) is caused by inactivating mutations in the phosphate-regulating endopeptidase homolog, X-linked (PHEX) gene, resulting in an excess of circulating intact fibroblast growth factor-23 (iFGF-23) and renal phosphate wasting. In the present study, we retrospectively reviewed the clinical and molecular features of 153 Chinese patients, representing 87 familial and 66 sporadic cases with XLH. A total of 153 patients with XLH presented with signs or symptoms at a median age of 18.0 months (range, 9.0 months–26.0 years). Lower-limb deformity was the most frequent clinical manifestation, accounting for 79.1% (121/153). Biochemical screening showed increased serum levels of iFGF23 in patients with XLH, with a wide variation ranging from 14.39 to 730.70 pg/mL. Median values of serum iFGF23 in pediatric and adult patients were 94.87 pg/mL (interquartile range: 74.27–151.86 pg/mL) and 72.82 pg/mL (interquartile range: 39.42–136.00 pg/mL), respectively. Although no difference in circulating iFGF23 levels between these two groups was observed (P=0.062), the proportion of patients with high levels of circulating iFGF23 (> 42.2 pg/mL) was greater in the pediatric group than in the adult group (P=0.026). Eighty-eight different mutations in 153 patients were identified, with 27 (30.7%) being novel. iFGF23 levels and severity of the disease did not correlate significantly with truncating and nontruncating mutations or N-terminal and C-terminal PHEX mutations. This study provides a comprehensive description of the clinical profiles, circulating levels of iFGF23 and gene mutation features of patients with XLH, further enriching the genotypic spectrum of the diseases. The findings show no evident correlation of circulating iFGF23 levels with the age or disease severity in patients with XLH.